ANALISIS FAKTOR-FAKTOR PENERAPAN LEAN CONSTRUCTION PADA PROYEK KONSTRUKSI GEDUNG DI KOTA BANDA ACEH - Zulhelmi Andika; Muttaqin Hasan; Abdullah Abdullah (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Lean construction is a construction implementation method that can minimize waste and maximize value. In the implementation of building construction projects, especially in Banda Aceh City, there are still many contractors who stick to conventional implementation methods, although the government has introduced lean building methods. Traditional methods tend to produce waste and neglected value. This study aims to determine the dominant lean construction factors applied to building construction projects in Banda Aceh City. Construction using funds from the City's Revenue and Expenditure Budget (APBK) years of 2015-2021. Respondents in this study were targeted at project managers/construction managers from medium and high-skilled contractors in Aceh province with a population of 1,610 companies. A proportionally stratified random sample is used as the sampling method and 165 companies were selected as samples. The data analysis technique used descriptive statistics, validity test, reliability test, and Principal Component Analysis (PCA) using Statistical Product and Service Solution (SPSS) software. The results showed that the lean construction factors applied to building construction projects in Banda Aceh City included 7 factors namely the implementation method, material control, supply chain, time management, documentation, teamwork, and communication factors with a  variance (percentage of application) of 61.770%. The dominant lean construction factor applied to building construction projects in Banda Aceh is the implementation method factor, with a variance of 17.593%.